Formation of Trans-Activation Competent HIV-1 Rev:RRE Complexes Requires the Recruitment of Multiple Protein Activation Domains - Hoffmann, Dirk (Public Library of Science, 2012)
The HIV-1 Rev trans-activator is a nucleocytoplasmic shuttle protein that is essential for virus replication. Rev directly binds to unspliced and incompletely spliced viral RNA via the cis-acting Rev Response Element (RRE) sequence. Subsequently, Rev oligomerizes cooperatively and interacts with the cellular nuclear export receptor CRM1. In addition to mediating nuclear RNA export, Rev also affects the stability, translation and packaging of Rev-bound viral transcripts. Although it is established that Rev function requires the multimeric assembly of Rev molecules on the RRE, relatively little is known about how many Rev monomers are sufficient to form a trans-activation competent Rev:RRE complex, or which specific activity of Rev is affected by its oligomerization. We here analyzed by functional studies how homooligomer formation of Rev affects the trans-activation capacity of this essential HIV-1 regulatory protein. In a gain-of-function approach, we fused various heterologous dimerization domains to an otherwise oligomerization-defective Rev mutant and were able to demonstrate that oligomerization of Rev is not required per se for the nuclear export of this viral trans-activator. In contrast, however, the formation of Rev oligomers on the RRE is a precondition to trans-activation by directly affecting the nuclear export of Rev-regulated mRNA. Moreover, experimental evidence is provided showing that at least two protein activation domains are required for the formation of trans-activation competent Rev:RRE complexes. The presented data further refine the model of Rev trans-activation by directly demonstrating that Rev oligomerization on the RRE, thereby recruiting at least two protein activation domains, is required for nuclear export of unspliced and incompletely spliced viral RNA.